Mechanical properties and rapid consolidation of binderless nanostructured tantalum carbide - Kim, Byung-Ryang; Woo, Kee-Do; Doh, Jung-Mann; Yoon, Jin-Kook; Shon, In-Jin (ELSEVIER SCI LTD, 2009)
The rapid sintering of nanostructured TaC hard material was investigated with a focus on the manufacturing potential of high-frequency induction heated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and prohibition of grain growth in nanostructured materials. A dense pure TaC hard material with a relative density of up to 96% was produced with simultaneous application of 80 MPa pressure and induced current within 3 min. The finer the initial TaC powder size, the higher the density and the better mechanical properties. The fracture toughness and hardness values obtained from 10 h milled powder were 5.1 +/- 0.3 MPa m(1/2) and 22 GPa, respectively, under 80 MPa pressure and 80% output of total power capacity (15 kW). (c) 2009 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: HARD MATERIALS; WC